If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -5) + (9x + 2) = (4 + -6x) + -1(7x + 8) Reorder the terms: (-5 + 4x) + (9x + 2) = (4 + -6x) + -1(7x + 8) Remove parenthesis around (-5 + 4x) -5 + 4x + (9x + 2) = (4 + -6x) + -1(7x + 8) Reorder the terms: -5 + 4x + (2 + 9x) = (4 + -6x) + -1(7x + 8) Remove parenthesis around (2 + 9x) -5 + 4x + 2 + 9x = (4 + -6x) + -1(7x + 8) Reorder the terms: -5 + 2 + 4x + 9x = (4 + -6x) + -1(7x + 8) Combine like terms: -5 + 2 = -3 -3 + 4x + 9x = (4 + -6x) + -1(7x + 8) Combine like terms: 4x + 9x = 13x -3 + 13x = (4 + -6x) + -1(7x + 8) Remove parenthesis around (4 + -6x) -3 + 13x = 4 + -6x + -1(7x + 8) Reorder the terms: -3 + 13x = 4 + -6x + -1(8 + 7x) -3 + 13x = 4 + -6x + (8 * -1 + 7x * -1) -3 + 13x = 4 + -6x + (-8 + -7x) Reorder the terms: -3 + 13x = 4 + -8 + -6x + -7x Combine like terms: 4 + -8 = -4 -3 + 13x = -4 + -6x + -7x Combine like terms: -6x + -7x = -13x -3 + 13x = -4 + -13x Solving -3 + 13x = -4 + -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. -3 + 13x + 13x = -4 + -13x + 13x Combine like terms: 13x + 13x = 26x -3 + 26x = -4 + -13x + 13x Combine like terms: -13x + 13x = 0 -3 + 26x = -4 + 0 -3 + 26x = -4 Add '3' to each side of the equation. -3 + 3 + 26x = -4 + 3 Combine like terms: -3 + 3 = 0 0 + 26x = -4 + 3 26x = -4 + 3 Combine like terms: -4 + 3 = -1 26x = -1 Divide each side by '26'. x = -0.03846153846 Simplifying x = -0.03846153846
| 10x+2y=0 | | 5e^3x=19 | | 3+7p-2=9p+26-7p | | 3x^2-4xy+7y^2=13 | | -5(-8a-6)-(-4a+12)-6(2a-9)= | | x^3+2x^2-8x-48=0 | | x^3-2x^2-8x-48=0 | | 3/x+12x=0 | | 3a+2b=-2 | | -5x+9x=3+17 | | 6/2x=-2 | | 6-2xy=-2 | | 38-7x=2x+17 | | 4-5x=-19 | | 3x+5=-x | | 5-10=153-38x | | 5x-7y+31=0 | | -2t^3=60t-26t^2 | | 3x+10=-67+-8x | | 3x+10=67-8x | | x^2+8y-4z=134 | | 16t^2+5776=0 | | -16t^2+3600=0 | | 3(2x+2)-9=-33 | | (16+2x)(20+2x)=480 | | (16+2x)(20+2x)=320 | | F=-4(c+3)+(6c-5)c | | -3(x-3)+x=8(9-x) | | E=2z(5+3z)-4 | | x(x-3)=x^2+8x+9 | | 4x+38=4 | | d=-2(y-8) |